Habitat preferences of brown mudfish (Neochanna apoda Günther) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Conservation Biology at Massey University, Palmerston North, New Zealand - Petrove, Natasha Katherine (Massey University, 2009)
Brown mudfish (Neochanna apoda) are one of five non-diadromous mudfish species endemic to New Zealand. They are considered a ‘vulnerable’ species under human induced gradual decline (Hitchmough et al., 2007; IUCN, 2009). Brown mudfish are the most widely distributed Neochanna species in NZ, however, their populations within this range are patchy. A lowland swamp fish species, brown mudfish are historically noted to be found in forested wetland areas, such as kahikatea (Dacrycarpus dacrydioides) swamp-forest. Clearance, drainage and modification of around 90% of lowland wetland areas in NZ (McGlone, 2009) has resulted in habitat loss, with populations now found in the widest range of habitat types of all the NZ Neochanna species. Habitat suitability is hard to assess for brown mudfish as they subsist in such a wide range of habitats. Habitat preferences were investigated to determine which habitat characteristics were most influential for brown mudfish. Geographic Information Systems (GIS) data and nationwide records from the New Zealand Freshwater Fish Database (NZFFD) were used for this analysis. Substrate type, rainfall, shading and low slopes were important aspects for sites with brown mudfish present. Sites without mudfish had steep slopes, high elevation catchments, a large substrate size and warm temperatures. Historical land cover and shading were also important in determining brown mudfish distribution. A local study found some GIS variables to be useful for predicting brown mudfish presence, but on-site measures of ephemerality and flowing water were the most important habitat features for brown mudfish. Brown mudfish are not often found with other fish species and are considered poor competitors (O’Brien and Dunn, 2007), suggesting that presence of other fish species influences brown mudfish presence. Continued wetland modification increases the probability of brown mudfish encountering other species. The ability of brown mudfish to detect shortfin eels (Anguilla australis; a natural predator), and the response made once detection occurred, was investigated. Mudfish were presented with a choice between eel odour or neutrally odoured water. The response made varied with mudfish size. The varying responses indicate that brown mudfish are able to detect shortfin eels, and that this is likely to be a learned behaviour.
Keywords: Brown mudfish; Neochanna apoda Günther; Habitat; New Zealand; Fields of Research::270000 Biological Sciences::270700 Ecology and Evolution::270701 Freshwater ecology